New Broadband L-Shaped CPW-Fed Circularly Polarized Monopole Antenna With Asymmetric Modified Ground Plane And A Couple Series-Aligning Inverted L-Shaped Strip - Zakaria, Zahriladha; Awang Md Isa, Azmi; Alsariera, Hussein (Elsevier GmbH, 2020)
A new compact coplanar waveguide (CPW) -fed broadband circularly polarized (CP) monopole antenna is proposed in this study. The antenna structure is composed of an L-shaped monopole, an asymmetric modified ground plane and a couple series-aligning inverted L-shaped strip. The modification of cutting two slots in the asymmetric ground plane achieves a wide CP bandwidth, and a couple series-aligning inverted L-shaped strip is introduced with the left ground plane to achieve broadband impedance bandwidth (IBW). A - 10 dB IBW of 103% (2–6.2 GHz) and 3 dB axial ratio bandwidth (ARBW) of 98% (1.9– 5.85 GHz) is achieved. The antenna design process and the parametric study are presented, and the CP mechanism is analyzed.